The Musicality of Campursari Music in the Islamic Ritual Context - Bambang Sunarto (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2020)
This article discusses campursari’s music, which has an increasingly broad role, from profane to sacrilegious Islamic areas. Since its birth, this music serves as entertainment music. In the era of the 1990s and its peak in the 2000s, this music entered and interacted with the Islamic community. The entry of campursari music into the Islamic religious community is the embodiment of expectations and demands for environmental situations and conditions. Hopes and needs give birth to musical syncretism, which gives birth to adaptation strategies. Verstehen are appropriate methods for recognizing forms of adaptation and syncretism. The choice of the verstehen method is because this article does not merely highlight the problem of music, but also tries to understand the social actions of campursari musicians in serving the muslim community via campursari music. The choice of this approach is because musical adaptation stems from the idea that the birth of musicality has the support of a socially developed network of meanings. The benefit is to recognize the principles and rules of adaptive value and productive syncretism that occur behind music phenomena. The results of this study indicate that campursari's performance is sufficient to prove that campursari's musical musicality in the context of Islamic rituals is productive syncretism. Adaptation and syncretism are thus two methods and ways of building products, both of which must co-exist.